Perbaikan Lahan Tailing Pasir Pascatambang Timah dengan Kompos Tandan Kosong Kelapa Sawit untuk Budidaya Lada Perdu (Piper nigrum L.) - Joni Iskandar; Ismed Inonu; Ratna Santi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Iskandar J, Inonu I, Santi R. 2020. Utilization of oil palm empty fruits bunches (OPEFB) compost for improvement of post-tin mining sand tailings in shrub pepper cultivation (Piper nigrum L). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the efforts made to obtain the need for pepper cultivation land is by utilizing ex-tin mining land which is quite extensive but has low fertility. To improve soil quality, amelioration was carried out using compost of oil palm empty bunches (OPEFB). The purpose of this study was to determine the effect of OPEFB compost dosage on post-tin mining sand tailings on the growth of shrub pepper and to obtain the proper OPEFB compost dose. This study used an experimental method with a single randomized block design (RBD). The factors studied were the dosage of OPEFB compost consisting of 2 tonnes/ha, 4 tonnes/ha, 6 tonnes/ha, 8 tonnes/ha, 10 tonnes/ha and 12 tonnes/ha. The data obtained were tested with ANOVA α = 5% and DMRT α 5%. The results showed that the dosage of OPEFB compost had a significant effect on the increase in stem diameter, but had no significant effect on the variables of increase in the number of leaves, the number of secondary branches, the increase in the number of internodes, the chlorophyll content, and the leaf area of the pepper shrub. Providing 12